Effectiveness and safety of surgical antibiotic prophylaxis in dental procedures in patients without underlying cardiac conditions: an overview of systematic reviews (Research, Society and Development, 2022)
Objective: This overview of systematic reviews aimed to assess the effectiveness and safety of surgical antibiotic prophylaxis for patients without underlying cardiac conditions undergoing dental surgical procedures. Methods: The searches were carried out at PubMed, Lilacs, Cochrane Library, Web of Science and Scopus databases. Systematic reviews of randomized controlled trials and non-randomized controlled trials that assessed the effectiveness and safety of surgical antibiotic prophylaxis in patients without underlying cardiac conditions undergoing dental surgical procedures were included in the study. A methodological quality assessment was carried out through AMSTAR-2. Results: The search resulted in 1910 studies and 15 systematic reviews were included in the overview. Three surgical procedures were identified: dental implant, dental extraction and endodontic surgery. Most systematic reviews (80%) did not present conclusive results on the effectiveness and safety of surgical antibiotic prophylaxis in procedures performed in patients without underlying cardiac conditions. Eleven studies showed low or critically low quality and four presented moderate methodological quality. Conclusion: The results are inconclusive to state that surgical antibiotic prophylaxis is more effective and safer for patients without underlying cardiac conditions undergoing dental implant, dental extraction and endodontic surgery compared to no intervention, as this overview of systematic review showed evidence that surgical antibiotic prophylaxis should be avoided in healthy patients to minimize the risk of antimicrobial resistance until studies with a lower risk of bias are available to support a favorable decision-making for use.